Bimbingan Kelompok Teknik Permainan Ular Tangga Bermuatan Humor untuk Mengurangi Stres Akademik Siswa SMK - Pramudita, Galuh Ayu; Atmoko, Adi; Hotifah, Yuliati (Indonesian Journal of Counseling and Development, 2025)
Academic stress is a common psychological state among students, particularly in Vocational High Schools, arising when academic demands overwhelm an individual's coping abilities. Left unmanaged, this stress can negatively affect students' psychological well-being and academic performance. This study aimed to develop a humorous "Snakes and Ladders" game and a group guidance service guide to help reduce academic stress levels in vocational high school students. The research employed the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, encompassing needs analysis, product design, expert validation, limited testing, and field implementation. Research subjects included subject matter experts, media experts, potential users (guidance and counseling teachers), and students from SMK Negeri 13 Malang. Data collection tools consisted of validation sheets, evaluation questionnaires, and participant reflections. Results indicated an average score of 1.00, demonstrating that the developed game media and guides had a "very high" level of feasibility in terms of accuracy, usability, ease of use, and appeal. In conclusion, the humorous "Snakes and Ladders" game media and group guidance guides are highly suitable for reducing academic stress among vocational high school students